DECENTRING THE HUMAN, IMAGINING THE MORE-THAN-HUMAN (Poetry, Plants, and the New England Region of Australia) - John Charles Ryan (LITERA, 2020)
Located in the state of New South Wales, Australia, the Northern Tablelands bioregion is a high plateau landscape unique for its geological, faunal, and floristic variety. Known widely as the New England of Australia, the Tablelands is “a strange, almost inverted landscape” of undulating plains aside steep chasms. This article analyzes poetry about the flora of the New England Tablelands region of New South Wales, Australia. The article focuses on the importance of plants and poetry to the biocultural heritage of Australia. The research objective was to understand the natural and cultural dimensions of Tablelands plants as expressed in poetry. The research involved visiting botanical communities, examining historical documents, interviewing conservationists, and writing poetry. The results suggest that poetry encourages engagement with, and respect for, human and more-than-human life. The article concludes that, in the Anthropocene age, environmental poetry is essential to environmental ethics. Keywords: poetry, ecopoetics, plants, New England Tablelands, Australia  MEMULIAKAN MANUSIA, IMAJINASI MELEBIHI BATAS KEMANUSIAAN(Puisi, Tanaman, dan Wilayah New England Australia) Abstrak               Terletak di negara bagian New South Wales, Australia, bioregion Tablelands Utara adalah lanskap dataran tinggi yang unik karena keanekaragaman geologis, fauna, dan floristiknya. Dikenal luas sebagai New England of Australia, Tablelands adalah "pemandangan aneh, lanskap yang hampir terbalik" dari dataran bergelombang dan jurang yang curam. Artikel ini menganalisis puisi tentang flora wilayah New England Tablelands di New South Wales, Australia. Artikel ini berfokus pada pentingnya tanaman bagi warisan biokultural Australia. Tujuan penelitian adalah untuk memahami dimensi alami dan budaya tanaman Tablelands seperti yang diungkapkan dalam puisi. Penelitian ini melibatkan mengunjungi komunitas botani; memeriksa dokumen sejarah; mewawancarai konservasionis; dan menulis puisi. Hasil penelitian menunjukkan bahwa puisi mendorong keterlibatan dengan, dan menghormati, kehidupan manusia dan lebih dari-manusia. Artikel itu menyimpulkan bahwa, di zaman Anthropocene, puisi lingkungan sangat penting bagi etika lingkungan.   Kata kunci: puisi, ekopuisi, tanaman, New England Tablelands, Australia